1995
DOI: 10.1111/j.1553-2712.1995.tb03218.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Warming and Buffering on Pain of Infiltration of Lidocaine

Abstract: To reduce the pain of lidocane infiltration, buffering is more effective than warming. Warming does not enhance buffering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0
6

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 10 publications
0
45
0
6
Order By: Relevance
“…Whereas a multitude of investigators have championed other techniques such as altering the rate of infiltration [14,36], distraction methods, buffering [16-19, 37, 38] and warming the anaesthetic agents [39][40][41][42] in a variety of settings, there is no clear consensus as to the best method to reduce infiltrative pain, as no-one has sought to combine all these techniques in a prospective randomised study. Some studies have demonstrated that warm buffered anaesthetic agents induce less pain during infiltration than either warmed or buffered agents used in isolation, and that buffering solutions is preferable to warming the anaesthetic agents [9,12,13]. However, it is difficult to make comparisons between these studies as considerable heterogeneity exists in the volume of infiltrate, the technique and anatomical location of infiltration, and the method of warming and buffering procedures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas a multitude of investigators have championed other techniques such as altering the rate of infiltration [14,36], distraction methods, buffering [16-19, 37, 38] and warming the anaesthetic agents [39][40][41][42] in a variety of settings, there is no clear consensus as to the best method to reduce infiltrative pain, as no-one has sought to combine all these techniques in a prospective randomised study. Some studies have demonstrated that warm buffered anaesthetic agents induce less pain during infiltration than either warmed or buffered agents used in isolation, and that buffering solutions is preferable to warming the anaesthetic agents [9,12,13]. However, it is difficult to make comparisons between these studies as considerable heterogeneity exists in the volume of infiltrate, the technique and anatomical location of infiltration, and the method of warming and buffering procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The infiltration of local anaesthesia is the most painful part of such procedures and pain associations quickly develop into avoidance behaviours, with implications for future procedures [6][7][8]. Anxiety induced by preceding infiltrative pain is counterproductive [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…113 Injected local anesthetics may be required for additional anesthesia. Methods to decrease pain and distress from injection of local anesthetics include keeping needles out of sight of the child (especially the large-gauge needle used to draw up the anesthetic), buffering lidocaine with sodium bicarbonate in a 9:1 ratio, 114,115 warming the local anesthetic, 115 using a small-gauge needle (27 to 30 gauge), 116 injecting slowly, 117 injecting from wound edges rather than through intact skin, 118 and counterirritating surrounding skin during the injection. 119 Mixing bupivacaine with lidocaine or using lidocaine with epinephrine (except where contraindicated) increases the duration of anesthesia.…”
Section: Pharmacologic Interventionsmentioning
confidence: 99%
“…It is interesting to note that much of the existing literature regarding the buffering of lidocaine to reduce pain involves lidocaine solutions without epinephrine (13)(14)(15)(16)(17)(18)(19). The addition of epinephrine and the necessary preservatives decreases the pH of the solution and, therefore, increases the potential beneficial effect of buffering (13,14,20,21).…”
Section: (3) Error Bars Represent 95% Cismentioning
confidence: 99%